(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article discusses the influence of the theory of Tathagatagarbhi on the development and formation of philosophical teachings of schools of Chinese Buddhism. Also, the impact of the Tathagatagarbhi theory on the development of Far Eastern philosophical thought is described.